Paraparesis as initial manifestation of a Prototheca zopfii infection in a dog. (7th February 2014) - Font, C.; Mascort, J.; Márquez, M.; Esteban, C.; Sánchez, D.; Durall, N.; Pumarola, M.; Luján, A.
<x xml:space="preserve">Abstract</x> A case of protothecosis causing non‐ambulatory paraparesis in a dog without clinical evidence of disseminated infection is described. A five‐year‐old female Labrador retriever was referred with a 10‐day history of progressive non‐ambulatory paraparesis and lumbar pain as the only physical and neurological abnormalities. Lumbar myelography revealed severe extradural spinal cord compression extending from L4 to L7 vertebrae, and a right hemilaminectomy was performed. Surgical findings included an adherent whitish hard ill‐defined mass. Cytology and biopsy results disclosed the presence of algae enclosed in a matrix of chronic inflammatory infiltrate. Culture confirmed the presence of Prototheca species. Neurological improvement occurred within a month, and the dog received antifungal treatment without evidence of clinical disseminated disease for 6 months, but died after a generalised tonic–clonic seizure. Post‐mortem examination revealed multiple foci of inflammatory granulomatous infiltrate and algae‐like structures in the brain, lumbar intumescence and cauda equina. Prototheca zopfii was identified using molecular biology methods.